Переохлаждение при кристаллизации висмута в многослойных плёнках Cu-Bi-Cu и C-Bi-C - Дукаров, С.В.; Петрушенко, С.И.; Сухов, В.Н.; Чурилов, И.Г. (ХНУ имени В.Н.Каразина, НФТЦ МОН и НАНУ, 2013)
В работе методами измерения электросопротивления и in situ электронографии проведено исследование фазовых переходов плавление-кристаллизация в тонких слоях висмута, находящихся между сплошными толстыми плёнками меди и углерода. Определены величины предельного переохлаждения жидкой фазы в исследуемых слоистых системах. Обнаружены различия в кинетике кристаллизации расплава висмута в медной и углеродной матрицах, обусловленные различным контактным взаимодействием компонентов. У роботі методами вимірювання електричного опору та in situ електронографії проведено дослідження фазових перетворень плавлення-кристалізація в тонких шарах вісмуту, що знаходяться між суцільними товстими плівками міді та вуглецю. Визначено величини максимального переохолодження рідкої фази в досліджуваних багатошарових плівках. Виявлено відмінності у кінетиці кристалізації розплаву вісмуту у мідній та вуглецевій матрицях, обумовленні різною взаємодією компонентів. The paper, with the methods of measurement of electrical resistance and in situ electron diffraction, was studied the phase transitions melting-crystallization in thin layers of bismuth, that are located between thick continuous films of copper and carbon. It has been determined the value of limiting supercooling during the crystallization of bismuth in contact with copper and carbon. There has been detected the differences in the kinetics of crystallization of a melt of bismuth in the copper and carbon matrixes which are caused by the various contact interaction of the components.
Supercooling During Crystallization of Bismuth in Multilayer Film Cu-Bi-Cu and C-Bi-C
Keywords: Thin films; crystallization; Supercooling; in situ electron diffraction